Effective pretreatment of sugarcane bagasse with combination pretreatment and its hydrolyzates as reaction media for the biosynthesis of ethyl (S)-4-chloro-3-hydroxybutanoate by whole cells of E. coli CCZU-K14. (July 2016) - He, Yu-Cai; Zhang, Dan-Ping; Di, Jun-Hua; Wu, Yin-Qi; Tao, Zhi-Cheng; Liu, Feng; Zhang, Zhi-Jun; Chong, Gang-Gang; Ding, Yun; Ma, Cui-Luan
Graphical abstract: Highlights: Hydrolyzates was used instead of glucose for the bioreduction of COBE. Hydrolyzates promoted initial reaction rate and intracellular NADH content. Effective biosynthesis of ( S )-CHBE (∼500 g/L) was in hydrolyzate media. Abstract: In this study, sugarcane bagasse (SB) was pretreated with combination pretreatment (e.g., sequential KOH extraction and ionic liquid soaking, sequential KOH extraction and Fenton soaking, or sequential KOH extraction and glycerol soaking). After the enzymatic hydrolysis of pretreated SBs, it was found that all these three concentrated hydrolyzates could be used for the asymmetric bioreduction of ethyl 4-chloro-3-oxobutanoate (COBE) into ethyl ( S )-4-chloro-3-hydroxybutanoate [( S )-CHBE]. Compared with glucose, arabinose and cellobiose couldn't promote the initial reaction rate, and xylose could increase the intracellular NADH content. Moreover, it was the first report that hydrolyzates could be used for the effective biosynthesis of ( S )-CHBE (∼500 g/L; 98.0% yield) from 3000 COBE by whole cells of Escherichia coli CCZU-K14 in the presence of β-CD (0.4 mol β-CD/mol COBE), l -glutamine (200 mM) and glycine (500 mM). In conclusion, it is a new alternative to utilize bioresource for the synthesis of key chiral intermediate ( S )-CHBE.